2020
DOI: 10.1177/1049909120966619
|View full text |Cite
|
Sign up to set email alerts
|

Too Much Too Late? Chemotherapy Administration at the End of Life: A Retrospective Observational Study

Abstract: Purpose: Cancer treatment for those nearing death has become increasingly aggressive over time despite evidence that less aggressive approaches are associated with better quality of life and sometimes longer survival. Chemotherapy administration in the last 14 days of life is one of the proposed benchmarks for quality of cancer care. The purpose of our study is to evaluate factors associated with aggressive cancer treatment in patients who died within 2 weeks of receiving chemotherapy. Methods: This retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 32 publications
1
8
0
5
Order By: Relevance
“…Hospitalization has traditionally been associated with significant use of health care resources at the EOL including previous studies in patients with advanced cancer treated with traditional chemotherapy having high rates of hospitalization associated with ICU care before death. 7,11,25 Similar to the studies with chemotherapy, our study corroborates data where patients receiving ICIs in the last 30 days of life also had high rates of death in the hospital and low hospice enrollment. 10,11 Early involvement by palliative care specialists can improve patient quality of life and survival and reduce aggressive end-of-life care.…”
Section: Discussionsupporting
confidence: 87%
“…Hospitalization has traditionally been associated with significant use of health care resources at the EOL including previous studies in patients with advanced cancer treated with traditional chemotherapy having high rates of hospitalization associated with ICU care before death. 7,11,25 Similar to the studies with chemotherapy, our study corroborates data where patients receiving ICIs in the last 30 days of life also had high rates of death in the hospital and low hospice enrollment. 10,11 Early involvement by palliative care specialists can improve patient quality of life and survival and reduce aggressive end-of-life care.…”
Section: Discussionsupporting
confidence: 87%
“…Questions about starting or not a chemotherapy treatment, proceed to the next cycle, differentiate symptoms caused by the disease from symptoms caused by the treatment, are very fine limits and, in clinical practice, make some decisions more difficult. The fact that there are no guidelines to guide the cessation of chemotherapy treatments, makes the decision extremely challenging [11]. In our study, no prognostic modifying factors were identified that could help the decision to continue or not with treatments, whether factors related to the disease or the patient.…”
Section: Discussionmentioning
confidence: 72%
“…This proportion of patients receiving treatment at end-of-life differs across cancer centres ranging from 2.88% to 15.7%. 4,8,9,[41][42][43] Our low baseline prevalence of aggressive cancer treatment at end-of-life is reassuring. There is however areas for improvement with respect to acute healthcare utilization at endof-life with 9.18% of decedents having ≥2 ED visits and 17.12% having ≥2 hospitalizations in their last 30 days of life.…”
Section: Discussionmentioning
confidence: 99%